From dichotomisation towards intersectionality in addressing covid-19. (28th November 2021) - Jung, Anne-Sophie; Haldane, Victoria; Neill, Rachel; Mei Jin Tan, Melisa; Abdalla, Salma M; Bartos, Michael; Shresha, Pami; Chua, Alvin Qijia; Nordström, Anders; Legido-Quigley, Helena
Abstract : Anne-Sophie Jung and colleagues argue that understanding mechanisms of response to the covid-19 pandemic as trade-offs reinforces false dichotomies and hamstrings attempts to create stronger and more equitable health systems